Answer:
The values for the two equations are x=-3 and y=1
Therefore the solution is (-3,1)
Explanation:
Given equations are
To solve the given equations by Substitution method :
We are using here to solve the given equations by Substitution method because equations (1) and (2) are equivalent ( it has same solution )
Therefore we can equate the two given equations or substitute the y value equation (1) in (2) we get
2x+7=-2x-5
Subtracting with -(2x-5) on both sides we get
2x+7-(-2x-5)=-2x-5-(-2x-5)
2x+7+2x+5=-2x-5+2x+5
4x+12=0 ( adding the like terms )
4x=-12
Therefore x=-3
Now substitute the value x=-3 in equation (1) we get
y=2(-3)+7
y=-6+7
Therefore y=1
The values are x=-3 and y=1
The solution is (-3,1)